2018
DOI: 10.1007/s10792-018-0823-4
|View full text |Cite
|
Sign up to set email alerts
|

Everything is ok on YouTube! Quality assessment of YouTube videos on the topic of phacoemulsification in eyes with small pupil

Abstract: YouTube videos on small pupil phacoemulsification have low complication rates when compared to the literature, although no reliable mechanical dilatation methods are used in almost half of these videos. Until YouTube's place in e-learning becomes clearer, we suggest that viewers be cautious regarding small pupil phacoemulsification videos on YouTube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Aykut et al, in their study where they examined YouTube videos of cataract surgeries performed on eyes with small pupils, found that only one of the videos had significant complications and one had minor complications. However, considering that the complication rate is normally higher in eyes with small pupils, concluded that such videos are published less frequently [ 17 ]. Similarly, no complications were found in any of the videos in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Aykut et al, in their study where they examined YouTube videos of cataract surgeries performed on eyes with small pupils, found that only one of the videos had significant complications and one had minor complications. However, considering that the complication rate is normally higher in eyes with small pupils, concluded that such videos are published less frequently [ 17 ]. Similarly, no complications were found in any of the videos in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a bias towards videos of simpler cases or cases without surgical complications. One study found lower rates in YouTube videos of surgical complications during cataract surgery in eyes with small pupils compared with the reported rates in the literature, and most videos did not use mechanic pupil dilators [32].…”
Section: Current Pitfallsmentioning
confidence: 95%
“…4 Previously, ophthalmologists presented studies on YouTube video quality regarding retinitis pigmentosa, cataract surgery, refractive surgery, strabismus, keratoconus, multifocal intraocular lens, keratoplasty and soft contact lenses. 4,5,6,7,8,9 To the best of our knowledge, no previous study has assessed YouTube videos about uveitis. Thus, the aim of our study was to evaluate the quality of YouTube videos addressing uveitis as educational resources for patients.…”
Section: Introductionmentioning
confidence: 99%